MITOCHONDRIAL CHOLESTEROL AND CANCER. (August 2021) - Garcia-Ruiz, Carmen; Conde de la Rosa, Laura; Ribas, Vicent; Fernandez-Checa, Jose C.
Abstract: Cholesterol is a crucial component of membrane bilayers that determines their physical and functional properties. Cells largely satisfy their need for cholesterol through the novo synthesis from acetyl-CoA and this demand is particularly critical for cancer cells to sustain dysregulated cell proliferation. However, the association between serum or tissue cholesterol levels and cancer development is not well established as epidemiologic data do not consistently support this link. While most preclinical studies focused on the role of total celular cholesterol, the specific contribution of the mitochondrial cholesterol pool to alterations in cancer cell biology has been less explored. Although low compared to other bilayers, the mitochondrial cholesterol content plays an important physiological function in the synthesis of steroid hormones in steroidogenic tissues or bile acids in the liver and controls mitochondrial function. In addition, mitochondrial cholesterol metabolism generates oxysterols, which in turn, regulate multiple pathways, including cholesterol and lipid metabolism as well as cell proliferation. In the present review, we summarize the regulation of mitochondrial cholesterol, including its role in mitochondrial routine performance, cell death and chemotherapy resistance, highlighting its potential contribution to cancer. Of particular relevance is hepatocellular carcinoma, whose incidence in Western countries had tripled in the past decades due to the obesity and type II diabetes epidemic. A better understanding of the role of mitochondrial cholesterol in cancer development may open up novel opportunities for cancer therapy.